Successful Management of Dystocia due to Fetal Anasarca in Osmanabadi Goat. - Koli, Anujkumar; Patil, Anil; Ramteke, Snehal; Naktar, Sonali; Pitlawar, Sanjeev (The Indian Journal of Animal Reproduction, 2023)
A three year old Osmanabadi goat was reported to the Veterinary Clinical Complex, Udgir with the history of difficulty in parturition. The case was handled by local quack. On per vaginal examination revealed the anasarcous monster which is removed with obstetrical manoeuver and the dam was treated with antibiotic, analgesics and fluid therapy. An uneventful recovery was seen after the treatment.
Keywords: Anasarca; Dystocia; fetal monster; Osmanabadi goat